Functional outcomes and local control are acceptable following hand‐sewn colo‐anal anastomoses for rectal cancer: Results of long‐term follow‐up. Issue 3 (17th August 2021) - Hudson, David; Entriken, Fiona; Hodder, Rupert; Warner, Michael
Abstract: Background: Rectal cancer that grows so close to the anal canal that an adequate distal margin cannot be achieved with a double‐stapled anastomosis (DSA) has been managed with abdominoperineal resection. Inter‐sphincteric dissection and hand‐sewn colo‐anal anastomoses (HSCAA) allows anastomosis in some cases where DSA is impossible. There are concerns that HSCAA may lead to complications, local recurrence and poor continence. Our aim was to assess our experience with HSCAA in terms of recurrence, complications, continence and quality of life. Methods: Consecutive patients at two metropolitan hospitals who underwent an ultra‐low anterior resection with hand‐sewn colo‐anal anastomoses for low rectal cancer during a 10‐year period were asked to complete a questionnaire which allowed continence and quality‐of‐life scores to be calculated. Recurrence and complication rates were obtained from a retrospective medical record review. Results: A total of 26 patients underwent HSCAA. Six patients were not sent a questionnaire (3 deaths, 1 with ileostomy, 1 with ileostomy reversal within 3 months and one who had transferred care to another hospital). Fifteen patients returned questionnaires. Local recurrence occurred in zero cases. Two developed systemic recurrence. Four patients developed anastomotic stricture and three had anastomotic leak. Median Faecal Incontinence Severity Index score was 28 and median FIQoL scores were 3.00, 2.78, 3.86 and 3.00. One patient wished that they had had a permanent stoma rather than anastomosis. Conclusion: HSCAA delivered good local control of rectal cancer and high avoidance of permanent stoma. Faecal continence is impaired; however, the results are acceptable to the majority of patients. Abstract : Traditionally low rectal cancers were managed with an abdominoperineal resection. Our paper suggests that functional and oncological outcomes are acceptable following a hand‐sewn colo‐anal anastomosis for low rectal cancers.